Hedging von Mengenrisiken in der Landwirtschaft - Wie teuer dur̈fen "ineffektive" Wetterderivate sein? - Oliver Mußhoff; Norbert Hirschauer (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2008)
– Since the mid-nineties, agricultural economists discuss the suitability of "weather derivatives" as hedging instruments for volumetric risks in agriculture. Contrary to traditional insurance contracts, the payoffs of such derivatives are linked to weather indices (e.g. accumulated rainfall or temperature over a certain period) that are measured objectively at a defined meteorological station. While weather derivatives thus circumvent the problem of moral hazard and adverse selection, weather derivative markets for the agricultural sector are still in their infancy all-over the world. Some economists attribute this to theoretical valuation problems and the lack of a pricing method which is accepted by all market participants. Others think that the low hedging effectiveness of (standardized and non-customized) weather contracts cripple the market. Motivated by the question of how weather derivatives should be priced to agricultural firms, this paper describes a risk programming model which can be used to determine farmers' willingness-to-pay (demand function) for weather derivatives. The model considers both the derivative's farm-specific risk reduction capacity and the individual farmer's risk acceptance. Applying it to the exemplary case of a Brandenburg farm reveals that even a highly standardized contract which is based on the accumulated rainfall at the capital's meteorological station in Berlin-Tempelhof generates a relevant willingness-to-pay. We find that a potential underwriter could even add a loading on the actuarially fair price that exceeds the loading level of traditional insurances. Since transaction costs are low compared to insurance contracts, this indicates that there may be a significant trading potential.
Keywords: 330; Wetter; Risiko; Zahlungsbereitschaftsanalyse; Derivat; Hedging; Portfolio-Management; Deutschland